Pengaruh Rasio Profitabilitas dan Rasio Aktivitas Terhadap Nilai Perusahaan Pada Perusahaan Sektor Properti dan Real Estate Yang Terdaftar di Bursa Efek Indonesia Periode 2021-2024 - Chirinna, Yeshana; Karlina, Eulin (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The property and real estate sector is one of the sectors listed on the Indonesia Stock Exchange that plays an important role in the economy. The growth of this sector is driven by the high demand for various types of properties such as residential houses, apartments, and offices, in line with the increase in population, creating investment opportunities for investors to invest their shares. This study aims to analyze the impact of profitability ratios and activity ratios on the value of companies in the property and real estate sector listed on the Indonesia Stock Exchange for the period 2021-2024. The sample was selected using the purposive sampling method, resulting in a total of 9 companies. The data collection technique used was documentation. This research uses a quantitative statistical approach with data analysis techniques including descriptive statistical analysis, classical assumption tests, hypothesis tests, coefficient of determination tests, and multiple linear regression analysis, using the SPSS version 24 program. The research results show that partially, the profitability ratio (ROA) has a positive and significant effect on the company's value (PBV), while the activity ratio (TATO) has no partial effect on the company's value (PBV). The profitability ratio (ROA) and the activity ratio (TATO) simultaneously affect the company's value (PBV).